Primerjalna analiza religioznosti - Toš, Niko (Teorija in praksa, 2000)
Deriving from data collected in seven Central European and Eastern European countries (Aufbruch der Kirchen, 1997), the author attempts to construct an original classification of religiosity. Firstly, he applies multi-variant and cluster methods to analyze a large number of items using separate national data sets (Poland, Croatia, Lithuania, Slovakia, Hungary, Czech Republic and Slovenia), as well as an aggregate data set. The results indicate three dimensions of religiosity: 'orthodoxy', 'faith in god' and 'faith in life after death' (deep religiosity). The second step represents an analysis of fifteen variables measuring the three dimensions of religiosity. They serve as basis for constructing a complex dimension consisting of three elements (non-religious, autonomously religious, church religious). The complex dimension was labelled 'intimate religiosity' and was confirmed by examining associations with other dimensions of religiosity and selected socio-demographic variable. Based on this classification a rank of seven countries is derived, according to the extent of their religiosity. Poland and Croatia stand at the top, while Czech Republic, Hungary and Slovenia at the bottom of classification. Slovenian data reveal that a fifth of respondents(19%) display church religiosity, another fifth (21%) autonomous religiosity and three fifths (60%) non-religiosity.
Keywords: vera; religija; religion; vernost; krščanstvo; Christianity; družbena vloga; katoličani; Central Europe; Srednja Evropa; Vzhodna Evropa; Eastern Europe; Slovenia; Slovenija; verniki; raziskave; primerjalne analize